IMPROVING SERVICE QUALITY OF CALL CENTER USING DMAIC METHOD AND SERVICE BLUEPRINT - Fino Wahyudi Abdul; Nining Purwatmini (Journal of Management and Business, 2016)
Customer satisfaction is an important factor to businesses, because it causes customers to constantly return to use the service. Customer satisfaction is also related to the quality of service received by the customer of the companys’ products or services. The problem of OC’s call center service quality happened at the first time a customer contacts the call center where waste of customer’s waiting time is detected. Service quality improvement methods used in the analysis of the waste of customers’ waiting time is the DMAIC and lean approach. Results showed that improvement is seen at the sigma level. The tools used are SIPOC, pareto diagram, CTQ, two proportion test, DOE, p-chart, and minitab-16. Service blueprint analysis is used to analyze and discuss the relationship between service quality improvement using DMAIC in service process, points of contact with customers, and the evidence seen by the customer service